Repatriating Polanyi: Market Society in the Visegrád States - Hann, Chris (Amsterdam University Press, 2019)
Karl Polanyi's "substantivist" critique of market society has found new popularity in the era of neoliberal globalization. The author reclaims this polymath for contemporary anthropology, especially economic anthropology, in the context of Central Europe, where Polanyi (1886-1964) grew up. The Polanyian approach illuminates both the communist era, in particular the "market socialist" economy which evolved under János Kádár in Hungary, as well as the post-communist transformations of property relations, civil society and ethno-national identities throughout the region. Hann's analyses are based primarily on his own ethnographic investigations in Hungary and South-East Poland. They are pertinent to the rise of neo-nationalism in those countries, which is theorized as a malign countermovement to the domination of the market. At another level, Hann's adaptation of Polanyi's social philosophy points beyond current political turbulence to an original concept of "social Eurasia".